Memory activism as advocacy for transitional justice: memory laws, mass graves and impunity in Spain - Hepworth, Andrea (International journal of transitional justice, 2023)
Transitional justice in Spain is still an ongoing process. This article examines the impact of memory laws and the rise of the radical right on transitional justice measures and the historical memory movement in Spain. It contends that the continued application of the 46/1977 Amnesty Law and the campaigning by radical right party Vox to repeal memory laws left a legal vacuum that precipitated interventions by memory activist groups. It is argued that these protest actions are a form of advocacy for participatory transitional justice. The article first focuses on Andalusia’s 2017 memory law and the rise of Vox in the region. Subsequently, it examines the effect of the state’s Democratic Memory Law (2022) on memory and justice measures and argues that both bottom-up approaches by civil society organizations and top-down measures by state actors are essential to transform Spain into a society anchored in the five pillars of transitional justice.